Recent advancement of bioinspired nanomaterials and their applications: A review - Wu, Gang; Hui, Xiaodan; Hu, Linhui; Bai, Yunpeng; Rahaman, Abdul; Yang, Xing-Fen; Chen, Chunbo (Frontiers in Bioengineering and Biotechnology, 2022)
With the advancement in the field of nanotechnology, different approaches for the synthesis of nanomaterials have been formulated, among which the bioinspired or biomimetic nanoplatforms have been utilized for different biomedical applications. In this context, bioinspired or biomimetic nanoparticles (NPs) have been synthesized in which the inspiration for synthesis is taken from nature or its components. Innovations in bioengineering tools and bio-conjugation chemistry have enabled scientists to develop novel types of such nanoplatforms. They have several advantages over normal synthesis protocols. In this review, we 1) summarized nanomaterial types and their advancements in bioinspired nanotechnology therapies; 2) discussed the major types, novel preparation methods, and synthesis progress of NPs in current biomedical fields; 3) gave a brief account of the need for synthesizing NPs via a bioinspired route rather than their common route; 4) highlighted the updated information on the biomimetic synthesis of different types of NPs; and 5) provided future perspectives in the synthesis of novel NPs for their potential applications in biomedical sciences.